Implementasi Pengelolaan Sampah Melalui Program Bank Sampah di Dinas Lingkungan Hidup Kabupaten Pohuwato (Studi Kasus: Bank Sampah Kecamatan Buntulia) - Saleh, Gretty Syatriani; Umuri, Hasman; Uno, Defrianto (Universitas Islam Darul Ulum Lamongan, 2025)
This study examines the implementation of solid waste management through the Waste Bank (Bank Sampah) program administered by the Environmental Agency (DLH) of Pohuwato Regency, Indonesia, with a case focus on Waste Banks in Buntulia District. Using a qualitative descriptive design, data were gathered through interviews, observations, and document review involving DLH officials, waste bank managers, health workers, and community members. The analysis applies Edward III’s policy implementation framework—communication, resources, disposition, and bureaucratic structure—to explain how the program operates, what supports it, and where gaps persist. Findings show that coordination across DLH and local actors, face-to-face outreach complemented by routine WhatsApp and meeting communication, and the availability of basic operational facilities (transport, scales, storage, and savings records) generally enable implementation. Implementers display strong commitment and service orientation, and internal standard operating procedures clarify workflows for receiving, weighing, recording, sorting, storing, and selling recyclables. Nevertheless, participation remains uneven due to differing awareness, incentives, and household sorting practices, while service regularity still needs strengthening. The study recommends more intensive public education, stronger inter-sector collaboration, and partnerships with recyclers and local SMEs to improve routine services, expand participation, and sustain program impacts particularly through village and health-service networks.